Weather and Climate Tools for Florida Agricultural Producers - Christian L. Miller; Kati Migliaccio (EDIS)
AE440, a 4-page illustrated fact sheet by Christian L. Miller and Kati Migliaccio, familiarize Florida’s agricultural producers with some of the weather and climate tools that are available via the Internet. Published by the UF Department of Agricultural and Biological Engineering, November 2008.